AEROBIC AND ANAEROBIC CAPACITY AMONG MIDDLE-DISTANCE AND LONG-DISTANCE RUNNERS - Maheshwadagi, Rajshekhar M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Aerobic and anaerobic capacities are critical determinants of performance in middle-distance and long-distance running. Middle-distance runners (800m-1500m) rely on both anaerobic and aerobic energy systems, whereas long-distance runners (5000m and above) primarily depend on aerobic metabolism. This study aims to compare the aerobic and anaerobic capacities of middle-distance and long-distance runners to understand their physiological adaptations and energy system contributions. The methodology involved assessing VO₂ max, lactate threshold, and anaerobic power output in a sample of competitive male and female runners. The results indicate significant differences in VO₂ max values, lactate accumulation, and recovery rates between the two groups, highlighting the importance of training specificity. This paper discusses the implications of these findings in sports science, training strategies, and performance enhancement for middle-distance and long-distance runners.